Morphological and Molecular Characterization of Paralongidorus sali Siddiqi, Hooper, and Khan, 1963 with a Description of the First-Stage Juvenile and Male of Longidorus jonesi Siddiqi, 1962 from China - Cai, Ruihang (J Nematol, 2018)
Longidorids are economically important plant-parasitic nematodes because several species are virus vectors. Populations of Paralongidorus sali and Longidorus jonesi, isolated from woody perennials of Hangzhou, Zhejiang, China, were characterized molecularly and morphologically. The morphometric data of the Chinese populations of both species were compared with other populations. The present study provided a first record of the occurrence of Paralongidorus in China coupled with description of the first-stage Juvenile and male of L. jonesi. Phylogenetic analysis based on 18S and D2–D3 expansion segments of 28S gene indicated that L. jonesi clustered with L. jonesi reported from Japan and P. sali grouped with P. bikanerensis from Iran. Considering the pathological and economic importance of this group of nematodes, the study emphasized the need of updated descriptions from accurately identified specimens, isolation of sufficient material for examination, and molecular and phylogenetic analysis for a better understanding and diagnostics of Longidorid nematodes.